The influence of childhood oral health problems on physical and psychosocial development - Arua, Samuel Oko; Ngwu, Chika Charity; Ucheka, Promise Ifeanyi (Orapuh Journal, 2023)
Oral health problems such as dental caries, periodontal disease, and congenital craniofacial deformities have short- and long-term effects on the general health of infants. Good oral health in children is very important as it has a great impact on their growth, general development, and quality of life. The purpose of this paper was to review the effects that the most common oral health problems found in children have on their physical and psychosocial development. A further aim was to highlight potential actions that could be taken to ensure the achievement of good oral health in children especially those with craniofacial deformities. We searched databases such as PubMed, Google Scholar, MEDLINE, Cochrane Library, and Microsoft Academic to obtain up-to-date literature for this review. We searched for, and reviewed articles published within the past ten years. The importance of prevention, early detection, and management of dental caries and periodontal disease in children cannot be overemphasized. Recognition and correction of developmental abnormalities are very important to the general well-being of children born with congenital craniofacial anomalies.